Pengaruh online marketing, content creator dan produk bundling terhadap minat beli produk Somethinc - Fadhliyah, Putri Nazilatul; Febriansah, Rizky Eka; Hariasih, Misti (Jurnal Akuntansi dan Manajemen, 2026)
This study aims to analyze how online marketing, content creators, and Product Bundling affect Purchase Intention for Somethinc skincare products. The approach applied is a descriptive quantitative method using purposive sampling and involving 100 respondents who are users of Somethinc products. Data were collected through a Likert scale-based questionnaire distributed via social media. Data analysis was conducted using the Partial Least Square (PLS) method through SmartPLS 3.0 software. The study found that Online marketing and Product Bundling have a positive and significant effect on Purchase Intention, while Content creators do not show a significant effect. These results confirm that effective digital marketing strategies and proper product bundling can drive consumer purchase intention, whereas the content produced by creators has not yet been able to exert a strong direct impact. This study is expected to serve as a reference for developing marketing strategies for beauty products in the digital era, particularly regarding the behavior of young consumers.